Emergency nurses´ knowledge, attitude and perceived barriers regarding pain Management in Resource-Limited Settings: cross-sectional study - Desale Tewelde Kahsay; Marianne Pitkäjärvi (BMC, 2019)
Abstract Background Pain is a common phenomenon among emergency patients which may lead to chronic pain conditions and alteration of physiological function. However, it is widely reported that proper pain assessment and management, which is often accomplished by adequately trained nurses reduce the suffering of patients. Therefore, the aim of this study was to assess the emergency nurses´ knowledge, attitude and perceived barriers regarding pain management. Methods A cross-sectional quantitative study design was applied to determine the nurses´ knowledge level, attitude and the perceived barriers related to pain management. Hundred twenty-six nurses from the emergency departments of seven referral hospitals of Eritrea participated in the study. Data were collected in August and September 2017. Both descriptive and inferential statistics were used to summarize and elaborate on the results. Result In general, the knowledge level and attitude of the emergency nurses was poor. The participants' correct mean score was 49.5%. Nurses with Bachelor's Degree had significantly higher knowledge and attitude level compared to the nurses at the Diploma and Certificate level of professional preparation (95% CI = 7.1-16.7 and 9.4-19.1; p <  0.001) respectively. Similarly, nurses who had previous training regarding pain scored significantly higher knowledge level compared to those without training (95% CI =1.82-8.99; p = 0.003). The highest perceived barriers to adequate pain management in emergency departments were measured to be overcrowding of the emergency department (2.57 ± 1.25), lack of protocols for pain assessment (2.45 ± 1.52), nursing workload (2.44 ± 1.29) and lack of pain assessment tools (2.43 ± 1.43). There was no significant difference in perceived barriers among nurses with different demographic characteristics. Conclusion The emergency nurses' knowledge and attitude regarding pain management were poor. Nurses with higher educational level and nurses with previous training scored significantly higher knowledge level. This indicates the need for nursing schools and the ministry of health to work together to educate nurses to a higher level of preparation for pain assessment and management.